Construction of ultrafine TiO2 nanoparticle and SnNb2O6 nanosheet 0D/2D heterojunctions with abundant interfaces and significantly improved photocatalytic activity. Issue 11 (11th May 2017) - Jin, Yu; Jiang, Deli; Li, Di; Chen, Min
Abstract : Novel well-dispersed ultrafine TiO2 nanoparticle/SnNb2 O6 nanosheet 0D/2D heterojunctions have been synthesized by a facile hydrothermal method. Abstract : Novel well-dispersed ultrafine TiO2 nanoparticle/SnNb2 O6 nanosheet (TiO2 /SNO) 0D/2D heterojunctions have been synthesized by a facile hydrothermal method. Ultrafine TiO2 particles with average sizes of around 9.3 nm were uniformly and tightly attached on the surface of SNO nanosheets with approximately 3.2 nm thickness. The photocatalytic activities of the TiO2 /SNO nanocomposite were evaluated for the degradation of rhodamine B (RhB) and a colorless antibiotic agent, tetracycline hydrochloride (TC), under visible light irradiation. The TiO2 /SNO heterojunctions show significantly promoted photocatalytic activity towards the degradation of RhB and TC compared with the bare TiO2 and SNO. This enhanced photocatalytic activity can be mainly ascribed to the formed substantial contact interface and matched energy band of the heterojunction, which could improve charge transfer efficiency and suppress photoelectron–hole recombination. On the basis of radical scavenger experiments, superoxide radicals and holes are suggested to play a critical role in the degradation over TiO2 /SNO heterojunctions. This work could be extended to the design of other 0D/2D heterojunction photocatalysts with the purpose of enhancing activity by coupling suitable wide and narrow band-gap semiconductors, which is inspiring for practical environmental purification.